Le lien affectif à l’élève et le travail invisible de care en éducation préscolaire et en enseignement primaire : entre désir et obligation - Bilodeau, Karine; Giguère, Emilie; Louise, St-Arnaud (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
This article explores the student/teacher affective connection in preschool and elementary school education. This study relies on a critical experientialist work theory and a feminist perspective to understand and conceptualize the invisible work upon which this affective connection rests: care work. The methodology relies on qualitative research, including individual and group interviews. The sample includes 25 preschool and elementary school teachers. On the one hand, this study reveals tensions as the affective connection with the students is both desired and valued by teachers and compulsory, implicitly embedding care work within Quebec’s school mission. On the other hand, this study conceptualizes care as work and reveals how this invisible care work is embedded in social relations of sex.